Promoting and Updating Food Frequency Questionnaire Tool to Measure Food Consumption and Nutrient Intake Analysis - Madani, Zahra; Moussavi Javardi, Maryam Sadat; Karandish, Majid; Movahedi, Ariyo (International journal of preventive medicine, 2021)
One of the problems that nutritionists have always faced in research projects is the analysis of food intake of the subjects. Various approaches have been proposed in which the use of food frequency is one of the most used in this field. Many tools have been proposed in this area that aim of present research is to update and optimize one of the most common forms mentioned above. In this study, we attempted to update and optimize the 147-item common food frequency questionnaire using USDA database. Moreover, the values of dietary antioxidant profiles, lipid ratios, dietary fat quality, atherogenic and thrombogenic indices, amino acids, flavonoids, and other requirements are included in the above tool to meet nutrition research needs. The re-analysis of the obtained data with USDA Bank showed no difference due to the similarity of the source of information and the accuracy of the above instrument was confirmed. Due to the applicability of this tool, it can be recommended to researchers to use the above tool. We hope to see the Iranian database in the coming years to optimize the above tools based on the Iranian bank.